From Berlin to Jerusalem - Professor David Amiran and the Atlas of Israel - Bar-Gal, Yoram (ERDKUNDE, 2004)
The atlas both symbolizes and perpetuates a disciplinary tradition that came into being through linking science and nationalism, a tradition assisted by using the technique of mapping to present different findings and claims. This combination was imported to Israel with the arrival of the German Group and its absorption into the institutions of authority and research. David Amiran’s role in the introduction of professional ideas from Germany and the design of the atlas into the national political consensus in Israel was crucial. In a country like Israel the most important instrument for carrying out cartographical work, such as the Israeli Survey was in the hands of the political authorities. The question that needs to be asked is whether the information held by the state has to be presented according to political criteria, that is in accordance with the government’s policies, or whether it should be open to criticism and scientific interpretation. Is it, in fact, possible to relate to information of this kind as information with no ideological bias on the part of the mapmaker? Is the creation of the map and its accompanying text nothing but the creation of the official language that this same political authority is attempting to instil into society in order to perpetuate its ideas? Do the technical instruments used to carry out the mapping held by a government body provide it with the exclusive use of the cartographical presentation content? And, if so, should one relate to every cartographical publication produced by such a body as being suspect of cartographical propaganda? Despite all the criticism and interpretation one must ultimately reiterate that, in relation to the period in which it appeared and even according to contemporary standards, the Atlas of Israel is a great scientific achievement for the State of Israel and its scientists. Its creators made an honest attempt to present information according to the best scientifically objective procedures and were apparently unaware that this aspiration contained within it subjective and ideological assumptions that influenced their professional decisions. One should not see this as something unusual when compared to other national atlases as we have noted in the introduction. When it comes to national atlases such considerations are connected with the survival of the nation, strengthening identification and the perpetuation of the regime’s power through utilizing the different presentations of knowledge, as already claimed by Foucault (1980).